2018
DOI: 10.3390/ijerph15050965
|View full text |Cite
|
Sign up to set email alerts
|

Sludge Biochar Amendment and Alfalfa Revegetation Improve Soil Physicochemical Properties and Increase Diversity of Soil Microbes in Soils from a Rare Earth Element Mining Wasteland

Abstract: Long-term unregulated mining of ion-adsorption clays (IAC) in China has resulted in severe ecological destruction and created large areas of wasteland in dire need of rehabilitation. Soil amendment and revegetation are two important means of rehabilitation of IAC mining wasteland. In this study, we used sludge biochar prepared by pyrolysis of municipal sewage sludge as a soil ameliorant, selected alfalfa as a revegetation plant, and conducted pot trials in a climate-controlled chamber. We investigated the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 94 publications
2
17
0
Order By: Relevance
“…Dong et al (2016) found that the amounts of soil organic carbon, total nitrogen, total phosphorus and available phosphorus were significantly increased when new alfalfa land was reclaimed from native sandy steppe. A pot experiment also indicated that planting alfalfa significantly increased the contents of soil organic matter, total nitrogen, available nitrogen, available phosphorus and available potassium (Luo et al, 2018). However, a long-term survey showed that the contents of soil organic carbon, total nitrogen, available phosphorus and soil nitrate nitrogen decreased within 10 years of continuous cropping of alfalfa but then increased after alfalfa grew for more than 10 years (Jiang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dong et al (2016) found that the amounts of soil organic carbon, total nitrogen, total phosphorus and available phosphorus were significantly increased when new alfalfa land was reclaimed from native sandy steppe. A pot experiment also indicated that planting alfalfa significantly increased the contents of soil organic matter, total nitrogen, available nitrogen, available phosphorus and available potassium (Luo et al, 2018). However, a long-term survey showed that the contents of soil organic carbon, total nitrogen, available phosphorus and soil nitrate nitrogen decreased within 10 years of continuous cropping of alfalfa but then increased after alfalfa grew for more than 10 years (Jiang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Soil microorganisms are important components of soil ecosystems, play a critical role in material cycling (Lupwayi et al, 2004; Bastida et al, 2017), and quickly respond to changes in soil physicochemical properties (Jiang et al, 2007; Xiao et al, 2017). However, studies related to soil microbial characteristics in alfalfa fields have been limited (Beauregard et al, 2010; Zhong et al, 2012; Luo et al, 2018). Jiang et al (2007) investigated the soil microbial properties under alfalfa continuous cropping fields in the Loess Plateau of China and found that soil microbial biomass and soil basal respiration decreased steadily from 3 years of alfalfa continuous cropping to 9 years but increased from 15 to 25 years.…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al (2016) found that the amounts of soil organic carbon, total nitrogen, total phosphorus and available phosphorus were significantly increased when new alfalfa land was reclaimed from native sandy steppe. A pot experiment also indicated that planting alfalfa significantly increased the contents of soil organic matter, total nitrogen, available nitrogen, available phosphorus and available potassium (Luo et al, 2018).…”
Section: Introductionmentioning
confidence: 90%
“…Soil microorganisms are important components of soil ecosystems, play a critical role in material cycling (Lupwayi et al, 2004;Bastida et al, 2017), and quickly respond to changes in soil physicochemical properties (Jiang et al, 2007;Xiao et al, 2017). However, studies related to soil microbial characteristics in alfalfa fields have been limited (Beauregard et al, 2010;Zhong et al, 2012;Luo et al, 2018). Jiang et al (2007) investigated the soil microbial properties under alfalfa continuous cropping fields in the Loess Plateau of China and found that soil microbial biomass and soil basal respiration decreased steadily from 3 years of alfalfa continuous cropping to 9 years but increased from 15 years to 25 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation